2011
DOI: 10.1074/jbc.m110.175364
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear Factor-κB (NF-κB) p65 Interacts with Stat5b in Growth Plate Chondrocytes and Mediates the Effects of Growth Hormone on Chondrogenesis and on the Expression of Insulin-like Growth Factor-1 and Bone Morphogenetic Protein-2

Abstract: Growth hormone (GH) stimulates growth plate chondrogenesis and longitudinal bone growth with its stimulatory effects primarily mediated by insulin-like growth factor-1 (IGF-1) both systemically and locally in the growth plate. It has been shown that the transcription factor Stat5b mediates the GH promoting effect on IGF-1 expression and on chondrogenesis, yet it is not known whether other signaling molecules are activated by GH in growth plate chondrocytes. We have previously demonstrated that nuclear factor-B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
29
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 38 publications
(32 citation statements)
references
References 43 publications
3
29
0
Order By: Relevance
“…The activation of NFκB followed by Akt phosphorylation plays an important role in the development of insulin resistance. 33 To confirm that NFκB pathway was implicated in the regulation of osteocalcin on autophagy and ER stress, we blocked NFκB pathway via pyrrolidinedithiocarbamate (PDTC), a known NFκB inhibitor and NFκB p65 siRNA, respectively, in mouse VECs and VSMCs in the presence of tunicamycin and osteocalcin. NFκB p65 siRNA-transfected cells exhibited reduced p65 protein expression compared with control siRNA-transfected cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The activation of NFκB followed by Akt phosphorylation plays an important role in the development of insulin resistance. 33 To confirm that NFκB pathway was implicated in the regulation of osteocalcin on autophagy and ER stress, we blocked NFκB pathway via pyrrolidinedithiocarbamate (PDTC), a known NFκB inhibitor and NFκB p65 siRNA, respectively, in mouse VECs and VSMCs in the presence of tunicamycin and osteocalcin. NFκB p65 siRNA-transfected cells exhibited reduced p65 protein expression compared with control siRNA-transfected cells (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…This results in chondrocyte catabolic actions and Sox9 downregulation [57]. In contrast, RELA/p65 , which is expressed in healthy SSCs and GPCs, was shown in vitro to promote cell survival and proliferation in response to growth hormone [58, 59]. This finding will merit in vivo validation in future studies.…”
Section: Beta-scaffold Transcription Factors With Minor Groove Conmentioning
confidence: 99%
“…More recently, Stat5 has been shown to be acutely phosphorylated in response to GH in growthplate chondrocytes (154), consistent with the presumption that Stat5 also participates in Igf1 transcription at the growth plate based upon the similar growth phenotypes in individuals with mutations of the GH receptor and Stat5b genes (127). Moreover, a role for nuclear factor (NF)-B p65 has been also revealed in a series of experiments by Wu et al (155). Their group demonstrated that both inhibition of nuclear factor-B (NF-B) activity by the inhibitor pyrrolidine dithiocarbamate and depletion of NF-B by targeted small interfering RNA eliminated the effects of GH on Igf1 expression and chondrocyte proliferation and differentiation.…”
Section: Tissue-specific Mechanisms Of Igf1 Gene Regulationmentioning
confidence: 71%